The Parts of Speech in Arabic According to Ibrahim Anis: Between the Conceptions of the Ancients and the Efforts of the Moderns - saoucha, laamr (El Omda in Linguistics and Discourse Analysis, 2018)
The language isn’t just a template of words and sentences, in whole it forms a linguistic format that its regular elements according to regular laws; because its format interact each other in difficult way which makes a complete and a convenient classification that’s also takes a division and a classification principles of that’s all regular so that taking all aspects of the regularity for these language elements. That’s makes the Arabic linguistics work so hard to find a rating and a classification of the Arabic words according to a certain rules, also they agreed to a fixed perception that’s its words are divided to: a noun, a verb and a letter; but their analyzes and explanations has often been multiple and different that perhaps leads to a review of this partitions of many modern linguistics. So in this paper we try to stand up on the quadrilateral division of the Arabic speech whish’s Ibrahim Anis ,its also to the most important critical criticisms that he submits to the triple division of Arab grammarians, and his views according to Arabic grammarians perception and the proposals of the modern linguistics